Uboczne skutki polonofilstwa, czyli o nieformalnych ambasadorach Francji. Rosa Bailly i stowarzyszenie Les Amis de la Pologne - Małgorzata Nossowska (Annales Universitatis Paedagogicae Cracoviensis. Studia Historicolitteraria)
France’s cultural diplomacy was carried out by the Service des Œuvres Françaises à l’Étranger (SOFE) through institutions such as schools, universities, and cultural and social organizations. Les Amis de la Pologne and its Secretary General, Rosa Bailly, became well-known for their work on behalf of Poland. As a result, they became informal ambassadors of French culture and language, influencing the perception and image of France in the eyes of the Polish public between 1919 and 1942. The activities of Les Amis de la Pologne and the popularity of Rosa Bailly in Poland serve as an example of the effective use of unconventional channels of cultural diplomacy by the French Ministry of Foreign Affairs.